Cardioprotective effect of bradykinin-induced preconditioning mediated by calcitonin gene-related peptide in isolated rat heart - Song Qiu-jing; Li Yuan-jian; Deng Han-wu (Acta Pharmacologica Sinica, 2016)
AIM: To study the mediation of calcitonin gene-related peptide (CGRP) in the cardioprotective effect of bradykinin-induced preconditioning in heart. METHODS: The isolated rat hearts were perfused in a Langendorff mode. The cardiac function and creatine kinase (CK) were measured. RESULTS: Pretreatment with bradykinin for 5 min caused an improvement of heart function and a decrease of CK release during reperfusion [CK was (0.18 +/- 0.06), (1.07 +/- 0.14), and (0.37 +/- 0.15) U.min-1.g-1/(wet wt) for control, ischemia-reperfusion, and bradykinin, respectively, P < 0.01], and the effect of bradykinin was abolished in the presence of icatibant acetate (Hoe140 1 mumol.L-1) or CGRP8-37 (0.1 mumol.L-1) [CK was (0.37 +/- 0.15), (1.01 +/- 0.23), and (1.07 +/- 0.23) U.min-1.g-1 (wet wt) for bradykinin, Hoe140, and CGRP8-37, respectively, P < 0.01]. Pretreatment with capsaicin also abolished the protection of bradykinin [CK was (0.30 +/- 0.04) and (1.14 +/- 0.12) U.min-1.g-1 (wet wt) for vehicle and capsaicin, respectively, P < 0.01]. CONCLUSION: The cardioprotective effect of bradykinin-induced preconditioning was related to stimulation of CGRP release in the rat.